Interactions Between Morel Cultivation, Soil Microbes, and Mineral Nutrients: Impacts and Mechanisms - Yiwen Fu; Muxin Fan; Haiyan Qin; Zeyu Zhang; Shijun Liu; Shuwen Wu; Yun Wang; Xia Yuan (Journal of Fungi)
Morel mushrooms (Morchella spp.) are prized for their nutritional and medicinal value. Despite extensive research on their cultivation, the species’ impacts on the soil microbiota and minerals remain unclear. This study systematically evaluated six Morchella species, analyzing their effects on soil physicochemical properties, microbial communities, and mineral nutrients levels. The results showed that yield varied significantly among the species, with an order of M. sextelata > M. exuberans > M. eximia > M. importuna > Mel-13 > Mel-21. Cultivation led to a consistent reduction in soil NO3−-N levels, particularly in M. eximia and Mel-13 (40–50% decrease), while NH4+-N levels did not change significantly, indicating mycelial nitrate preference. Mineral nutrient alterations exhibited distinct species-dependent patterns, with M. eximia showing the greatest increase in exchangeable Ca, while M. importuna and M. sextelata caused the most obvious decreases in available B. Morchella species exerted more pronounced impacts on fungal than bacterial communities, evidenced by significant reductions in alpha diversity—particularly in high-yield M. sextelata—suggesting species-specific fungal inhibition. At the phylum level, consistent depletion of Ascomycota but enrichment of Mortierellomycota were noted. Moreover, correlation analyses identified significant positive associations between morel yield and both fungal community diversity and exchangeable Ca content. This implies that Morchella species restructures soil fungal communities through nutrient competition and mineral-mediated regulation, with calcium acting as a key modulator. Overall, by elucidating the interconnected ‘Morchella species–microbe–mineral’ relationships, this study highlights Morchella species’ distinct regulation of soil microecology, providing valuable insights for the selection of optimized species like M. eximia and targeted soil management in morel cultivation.